Pharmacokinetics of cyclophosphamide and alkylating activity in man after intravenous and oral administration - Juma, F. D. (1979)
1 Plasma cyclophosphamide levels were estimated by gas-chromatography in seven patients following intravenous and oral cyclophosphamide administration. Plasma alkylating activity was determined by the nitrobenzyl pyridine (NBP) reaction. 2 The plasma T(½) after intravenous administration ranged from 5.97 to 12.37 h but after oral administration was shorter, 1.32-6.8 h. The mean total body clearance was 66.6 ml kg(-1) h(-1) after intravenous dosing and 93.1 ml kg(-1) h(-1) following oral dosing. V(d)β was 0.71 (0.10 s.d.) 1 kg(-1) suggesting that cyclophosphamide is distributed largely in body water. 3 The mean hepatic extraction ratio was 0.25, indicating a modest first pass metabolism. The metabolic clearance was 3.72 1 kg(-1) and the intrinsic hepatic clearance 5.17 1 kg(-1). 4 The mean renal clearance was 4.8 ml kg(-1) h(-1) with 6.5% of the administered dose excreted unchanged in the urine suggesting tubular reabsorption of cyclophosphamide. 5 The mean T(½) of plasma alkylating activity was 8.82 h, there being no significant difference following oral and intravenous administration. On average, 3.5 times the alkylating activity was produced by an oral dose of cyclophosphamide as compared to an intravenous dose. It is possible that this may reflect production of a different pattern of alkylating metabolites following cyclophosphamide administration by different routes. The clinical significance of these observations is unknown.